The impact of the embryonic molecular clock in early chick embryo elongation - Fernandes, Ana Cristina Maia (2018)
Embryo development is strictly regulated in time and space. One of the mechanisms by which cells have temporal information is the somitogenesis clock. During somitogenesis, somites are formed periodically from the pre-somitic mesoderm (PSM) along the antero-posterior axis. The periodicity of somitogenesis is regulated by an oscillatory gene network that operates within PSM with the same period as somite formation. A member of this network in chick is hairy1, a member of the Hairy and Enhancer of Split (HES) family of transcription factors. The role of Hes proteins in biological contexts is broad, namely in development and more recently in cancer. Previous work from our lab showed that Hairy1 overexpression in PSM precursors in gastrulation stages delays embryo development. To understand this phenotype, we started by evaluating the expression pattern of hairy1 mRNA in gastrulating embryos. hairy is dynamically expressed along the antero-posterior and medial-lateral axes of the primitive streak. To evaluate embryo elongation, we performed live-imaging of embryos cultured in two different techniques: Chapman and New. The embryo elongates continuously over time with an average rate of 159 ± 55 uum/h independently of the culture system. The PSM and segmented region contribute the most for total embryo elongation. To understand the impact of Hairy1 overexpression we electroporated the PSM precursors in gastrulation stages and evaluated embryo elongation over time. The preliminary data obtained suggests that Hairy1 overexpression delays embryo elongation. Our work provides a novel quantitative framework for embryo elongation which can be used for comparative studies of chick embryo development in different conditions. Also, it gives new insights on the role of Hairy1 during embryo development which could be important to better understand development and diseases, such as Cancer.